2013
DOI: 10.1117/1.oe.52.9.095104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of working gas pressure on interlayer mixing in magnetron-deposited Mo/Si multilayers

Abstract: By methods of cross-sectional transmission electron microscopy and small-angle x-ray scattering (λ ¼ 0.154 nm) the influence of Ar gas pressure (1 to 4 mTorr) on the growth of amorphous interfaces in Mo/Si multilayers (MLs) deposited by DC magnetron sputtering is studied. The significant reduction in the ML period, which is evident as a volumetric contraction, is observed in MLs deposited at Ar pressure where the mean-free path for the sputtered atoms is comparable with the magnetronsubstrate distance. Some re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 59 publications
(82 reference statements)
0
2
0
1
Order By: Relevance
“…In addition to the intermixing, the interface roughness is another factor crucial for reflectivity. It was shown that adjusting the pressure in the deposition step can significantly reduce the interface roughness in Mo/Si PMMs [45]. In addition, the roughness is also affected by the thickness of individual layers [46].…”
Section: Structural and Optical Propertiesmentioning
confidence: 99%
“…In addition to the intermixing, the interface roughness is another factor crucial for reflectivity. It was shown that adjusting the pressure in the deposition step can significantly reduce the interface roughness in Mo/Si PMMs [45]. In addition, the roughness is also affected by the thickness of individual layers [46].…”
Section: Structural and Optical Propertiesmentioning
confidence: 99%
“…In addition to the intermixing, the interface roughness is another factor crucial for reflectivity. It was shown that adjusting the pressure in the deposition step can significantly reduce the interface roughness in Mo/Si PMMs [45]. On the other hand, the roughness is also affected by the thickness of individual layers [46].…”
Section: Structural and Optical Propertiesmentioning
confidence: 99%
“…Из данных, приведенных в данном подразделе, следует, что для многослойной системы W-Si возможно 2 подхода к снижению взаимодействия на межфазных границах Si и W: 1) уменьшение энергии распыленных атомов, например путем понижения напряжения горения магнетронов либо повышения давления рабочего газа с целью термализации распыленных атомов [44]; 2) снижение скорости осаждения. Снижение энергии осаждаемых атомов может вызвать развитие шероховатости [45].…”
Section: механизм роста силицидных прослоекunclassified